Usability of Mobile Application for Implementing Genetic Counselling Intervention among Thalassemia Patients and Caregivers: A Case Study of Cyber Gen - Setiawan, Henri; Hidayat, Nur; Farihatun, Atun; Indriastuti, Marlina; Kurniawan, Rudi; Firmansyah, Andan; Andarini, Esti; Lutfi Sandi, Yudisa Diaz (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
Utilization of communication and information technology has been widely used in the health sector, especially nursing. As one of the nursing interventions for thalassemia patients and caregivers, genetic counseling is not only done face to face but can use android-based telenursing facilities through the complete features available in the Cyber Gen application. This study aims to measure the usability level of Cyber Gen application as an indirect genetic counseling medium for thalassemia patients. This application was developed with four main services: basic information about diseases, consultation rooms, social support, and direct surveys. This application is built using the Flutter Framework, the Dart programming language, and Cloud Firestore as the database. Usability was measured by using the System Usability Scale in two groups of 30 respondents each with an incidental sampling technique. The usability score shows 81.75 for personal users and 82.25 for counselor users with a 100% readiness level for use. These results indicate that the Cyber Gen application can be used to deliver genetic counseling intervention to thalassemia patients and caregivers.